2013
DOI: 10.1590/s1980-65742013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saccadic eye movements on postural control stabilization

Abstract: Abstract-Several structures of the central nervous system share involvement in both ocular and postural control, but the visual mechanisms in postural control are still unclear. There are discrepant evidences on whether saccades would improve or deteriorate stabilization of posture. The purpose of this study was to determine the influence of saccadic eye movements on postural control while standing in different basis of support. Twelve young adults stood upright in wide and narrow stances while performing fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
7
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 15 publications
9
54
7
8
Order By: Relevance
“…Furthermore, postural balance was found to improve more during saccade conditions. This result, which was derived from SEM and PEM conducted at a frequency of 0.5 Hz, differs from the findings of previous studies that reported improvements in postural balance from saccades conducted at a higher frequency of 1.1 Hz (Stoffregen et al 2007;Rodrigues et al 2013). Further research is required to explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, postural balance was found to improve more during saccade conditions. This result, which was derived from SEM and PEM conducted at a frequency of 0.5 Hz, differs from the findings of previous studies that reported improvements in postural balance from saccades conducted at a higher frequency of 1.1 Hz (Stoffregen et al 2007;Rodrigues et al 2013). Further research is required to explain this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, a low frequency of saccadic eye movements decreased sway compared with fixation, but saccades that were performed at a higher frequency caused a further decrease, suggesting that task demands are crucial for determining the effects of saccadic eye movements on balance control, as previously demonstrated for young adults (Rodrigues et al, 2013). This result could be attributable to the mechanisms involved in the visual stabilization of posture.…”
Section: Discussionsupporting
confidence: 50%
“…These participants swayed significantly less when searching to detect the location of a target within an image than when randomly looking at similar images and/or looking at a stationary dot [22], they swayed significantly less when searching a letter in a text than when randomly looking at a white panel [23,25]. They also swayed significantly less when they had to gaze a dot appearing either right or left at a constant frequency and amplitude relative to the control stationary-gaze task [16,24,[26][27][28] and when they had to perform only one saccade toward a target relative to the stationary-gaze task ( [10], Table 1). The significant reduction of body sway was found at least at one level of the body (COP, head, shoulder, lower-back), at least in one direction (anteroposterior, mediolateral) and at least in one of the dependent variables used (standard deviation, range, surface area, mean velocity, root mean square, COP-COM, Table 1).…”
Section: Results Published In Active Vision Tasksmentioning
confidence: 97%
“…In seven of the nine selected studies, participants stood comfortably with no requirement to sway as less as possible [22][23][24][25][26][27][28]. Participants were simply asked to perform both control and active vision tasks as naturally as possible, and these studies showed a reduction of spontaneous COP and/or body sway in the active vision task.…”
Section: Limits Of the U-shape Nonlinear Interaction Model To Explainmentioning
confidence: 99%